Emotional well-being and job related stress among prison staff - research blueprint - Novak, Tihana (Array, 2007)
In recent years job stress researchers have begun to pay increasing attention to the role of emotions as indicators of strain and well-being at work (e.g., Daley, & Parfitt, 1996 ; Daniels, Brough, Guppy, Peters-Bean, & Weatherstone, 1997 ; Sevastos, Smith, & Cordery, 1992 ; Wright & Doherty, 1998). Some theoretical frameworks are from a job stress perspective, in which emotions are presumed to mediate the effects of job stressors on strains (Spector, 1998) - job stressors lead to negative emotional responses, which in turn lead to various behavioral, physical, and psychological strains. Chronic exposure to negative emotions, particularly the high arousal ones, are associated with physiological effects that in the long-term might well lead to physical illness (Johansson, Aronsson, & Lindstrom, 1978). Van Katwyk and co. (1999) developed the Job-Related Affective Well-Being Scale (JAWS) for measuring the different affects that have an affect people’ s perceptions on their subjective job-related well-being. This scale is going to be evaluate (as Croatian version) and used in this research. The purpose of the research is to explore the dimensionality of prison staff job affect and to investigate how various emotions related to job stressors, since, by the nature of their job, the prison staffs are exposed to the different and specific types of stressors. This presentation is blueprint of research that is going to became doctoral dissertation.